A potential prognostic marker in primitive lung neuroendocrine tumor: A case report. Issue 3 (September 2020) - Russo, Luigi; Grilli, Bruna; Minopoli, Anita; Capozzi, Monica; Tafuto, Salvatore; Correra, Marco; Trillò, Giusy; Isgrò, Maria Antonietta; Cavalcanti, Ernesta
Background: The diagnosis and monitoring of primitive lung neuroendocrine tumors (lung pNETs) are usually performed by the measurement of serum chromogranin A (CgA) and urinary 5-hydroxyindolacetic acid (5-HIAA) levels. However, imaging techniques are necessary due to the poor diagnostic efficiency of the laboratory tests. Methods: A total-body computed tomography and bone scintigraphy scans showed multiple hepatic and bone metastases of a 55-year-old man affected by well-differentiated lung pNETs without severe initial symptoms. After diagnosis, he started therapy and was monitored with serum, urinary markers, and imaging techniques. Results: During follow-up, the urinary 5-HIAA levels did not significantly increase, while serum CgA and urinary para-hydroxyphenylacetic acid (pHPAA) levels (urinary organic acid physiologically present in the urines of healthy subjects) showed significant increases related to worsening clinical condition. Conclusions: The early increase in urinary pHPAA levels—usually not dosed in pNET patient monitoring—could be a promising prognostic marker.